2009
DOI: 10.1089/gtmb.2009.0108
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Fragile X Screening in Guatemala: Use of a New Blood Spot Polymerase Chain Reaction Technique

Abstract: Background: Because fragile X syndrome (FXS) is prevalent, it has become the subject of newborn and high-risk screening efforts. International screening, however, can be financially and logistically prohibitive, particularly in countries where resources may be scarce. Recently, we have developed a screening test on blood spot that can detect expanded alleles from the normal through the full mutation range in both males and females. It is accurate, rapid, inexpensive, and applicable on blood spots and therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Several studies have also been carried out in different populations of subjects including ID, AUT, or those with special educational needs, to both assess the prevalence of FXS among these populations and to identify subjects with FXS, which is very important for families. In the above studies, using both cytogenetic and molecular approaches, the full mutation rate varies between 0.5 and 16 % and the premutation rate varies between 0 and 0.8 % (Biancalana et al 2004; Blomquist et al 1985; Brown et al 1986; de Vries et al 1998; de Vries et al 1997; Hecimovic et al 2002; Major et al 2003; Mazzocco et al 1997; Mila et al 1997; Pandey et al 2002; Patsalis et al 1999; Pouya et al 2009; Reddy 2005; Schaefer and Lutz 2006; Sharma et al 2001; Syrrou et al 1998; Watson et al 1984; Yuhas et al 2009). A multicenter study conducted in Sweden (Blomquist et al 1985) found FXS in 16 % of boys with infantile autism, and a multicenter survey among individuals with autism found 13 % were positive for FXS (Brown et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also been carried out in different populations of subjects including ID, AUT, or those with special educational needs, to both assess the prevalence of FXS among these populations and to identify subjects with FXS, which is very important for families. In the above studies, using both cytogenetic and molecular approaches, the full mutation rate varies between 0.5 and 16 % and the premutation rate varies between 0 and 0.8 % (Biancalana et al 2004; Blomquist et al 1985; Brown et al 1986; de Vries et al 1998; de Vries et al 1997; Hecimovic et al 2002; Major et al 2003; Mazzocco et al 1997; Mila et al 1997; Pandey et al 2002; Patsalis et al 1999; Pouya et al 2009; Reddy 2005; Schaefer and Lutz 2006; Sharma et al 2001; Syrrou et al 1998; Watson et al 1984; Yuhas et al 2009). A multicenter study conducted in Sweden (Blomquist et al 1985) found FXS in 16 % of boys with infantile autism, and a multicenter survey among individuals with autism found 13 % were positive for FXS (Brown et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…These samples were previously screened to determine the prevalence rates of expanded alleles. Cohorts from Australia (n = 201) (28), Chile (n = 77), the United Arab Emirates (n = 263), Guatemala (n = 151) (29), Indonesia (n = 312) (30), Italy (n = 67), Mexico (n = 277), Spain (n = 358) (31), and the United States (n = 1,359) (32) were included. Individuals were recruited from the general population for the Italy, Spain, and United States samples.…”
Section: Participantsmentioning
confidence: 99%
“…DNA samples are amplified by PCR and analyzed for CGG triplet repeat number, along with Southern blot analysis for clinical diagnosis. Newer methods have also been developed including mass spectrometry-based methods for analysis of PCR digests or a methylation specific-quantitative melt analysis [21][22][23][24][25][26]. However, not all FM patients exhibit the same level of developmental, intellectual, or functional disability.…”
Section: Introductionmentioning
confidence: 99%